Identities of art education in contemporary India: Reality, Rhizome and Assemblage - Sharma, Manisha (Informática na educação teoria & prática, 2016)
In this paper, I present an understanding of art and visual culture education in India in a framework that employs Deleuze and Guattari’s theories. I place this research study in context of contemporary trends in education policy and political climates in India. I suggest that research on understanding art education practices in emerging geographies be conducted with a view to gain a cohesive social understanding, rather that isolated views on curriculum and pedagogy, with pre-determined understandings of what art education is, and what it does. The paper is structured in the following manner: After setting a context for this paper, I provide an overview of the study itself. I then describe the development of my own study exploring the identity of Indian art education and art educators using a hybrid lens of Vedanta philosophy and Deleuze and Guattari’s theories of rhizome and assemblage. Explaining these concepts, I illustrate an application of this theoretical lens towards reading art education practices both of my research participants, as well as of developments of art education in ontemporary India. This paper thus offers a strategy to conduct research in art education employing a rhizomatic approach to structuring research, and analyzing data using the concept of assemblage. I make these suggestions in order to make multiple experiences and voices within the research relevant and respected, especially when read in international and global contexts.